“The roads are sexless and genderless” A proposal for the incorporation of women in Communitary Public Space under the framework of the cantonal road infrastructure, Naranjo, Costa Rica - Pérez-Carrillo, Yolanda Pérez-Carrillo (2021)
This article presents a project proposal that seeks to operationally define a rele- vant strategy for the local municipal government to define actions so that wo- men from nearby localities are incorporated into education and training proces- ses that will allow them to join community organizational dynamics, in the first instance, and later on to municipal political structures as community-municipal links, in such a way that they can have an influence on local decisions. Five areas of education and training are taken up in order to provide a basis for the incorporation of women in issues related to the road, especially in rural areas, where women have been made invisible.